Adjunct Analgesic Use for Acute Pain in the Emergency Department. Issue 2 (February 2017) - Priano, James; Faley, Brian; Procopio, Gabrielle; Hewitt, Kevin; Feldman, Joseph
Purpose: Multimodal analgesia is common practice in the postoperative setting, but the utility of adjunctive analgesia in the emergency department (ED) is less understood. The primary objective of this study was to analyze ED prescriber ordering habits for adjunct nonopioid pain medication for opioid-naïve patients who require intravenous (IV) morphine or hydromorphone for acute pain. Secondary objectives were to assess initial and total opioid consumption in morphine equivalent units (MEU), pain scores, and ED length of stay (LOS) between groups. Methods: A retrospective chart review of adult patients who presented to the ED at a large academic medical center and received IV morphine or hydromorphone for acute pain was conducted. Patients were analyzed according to initial opioid received and presence or absence of adjunct nonopioid analgesics. Results: A total of 102 patient charts were analyzed. Adjunctive nonopioid analgesics were ordered on 38% of patients. Patients who received an adjunct nonopioid analgesic received a smaller mean initial opioid dose than those who did not (4.73 vs 5.48 MEU, p = .08). Initial pain score reduction on the 11-point Numeric Rating Scale (NRS) did not differ between patients who received adjunct analgesics versus those who did not (3 vs 4, p = .75). Patients who received adjunct analgesics were associated with a decreased ED LOS (294 vs 342 minutes, p = .04). Conclusion: A small proportion of patients with acute pain received a nonopioid analgesic in conjunction to IV opioids. Further studies are warranted to assess the impact of adjunct analgesics for patients with acute pain.